The effect of blended learning on enhancing motivation for academic achievement in students in the faculties of humanity sciences at hail university - Benayan Bani ALrasheedy; Abdalla Sayed Mohamed Gaballa; Kateb Alhamedi Alshammari; Hanouf Mohammed Alrashdi (Acta Psychologica)
This study aimed to investigate the effect of blended learning on enhancing motivation for academic achievement in students of humanity sciences (education and arts) at Hail University. The study used a quasi-experimental approach. A total of 80 students (60 men and 20 women) participated and 62 and 18 were from the education and arts faculties, respectively. Data on student performance were collected before and after the intervention through surveys and academic tests. Results indicated a significant improvement in motivation for academic performance post-application compared to pre-application, demonstrating a clear impact of blended learning. The findings provide strong evidence supporting the embracement of blended learning to enhance students' academic performance. Significant differences were observed in the academic ambition level, whereas no significant differences were noted in other dimensions and the total score based on faculty. These findings underscore the necessity for educational institutions to develop comprehensive blended learning programs and invest in them to fulfill students' diverse needs.